Translating news on cross-strait relations : a case study of journalistic translation based on selected news from the New York Times - Li, Jiayi (2019)
Journalistic translation is a specific translation field. Academic interest in journalistic translation began in the late 1980s and 1990s and thrived since 2000. Researchers carried out empirical research on translated news and analyzed its translation process. Through different channels, news can not only report and explain events happening around the world, but also express a point of view so as to stimulate a public opinion. This study focuses on the examination of journalistic translation with a selection of news articles on cross-strait relations between China and Taiwan as examples from the website of the New York Times. The analysis was based on the comparison between the translations done by the author of this paper and the official translations available on the website of New York Times. The results show that the translators of the news articles took different approaches and the effects of their translation results showed different focuses. In addition, it was also found that the results of the different approaches to translation were influenced by political or cultural factors, or the patronage received. The study concludes four characteristics in news translations, which are change in headlines, establishment of key ideas, addition of information, and domestication of translation. The exploratory nature of the study sets a perspective for future empirical research in journalistic translation that may enhance the value of integrated translation.